Biomimetics: Multilayered Lipid Membrane Stacks for Biocatalysis Using Membrane Enzymes (Adv. Funct. Mater. 17/2017). (2nd May 2017) - Heath, George R.; Li, Mengqiu; Rong, Honling; Radu, Valentin; Frielingsdorf, Stefan; Lenz, Oliver; Butt, Julea N.; Jeuken, Lars J. C.
Abstract : In article number 1606265 Lars J. C. Jeuken and co‐workers use a layer‐by‐layer assembly of lipid bilayers to multiply the surface concentration of electroactive membrane enzymes at electrodes. The interconnected membrane multilayers, akin to those of thylakoid membranes, create a material that exhibits a linear increase in bioelectrocatalytic activity with each additional enzyme‐containing membrane layer (containing either ubiquinol oxidase or an oxygen‐tolerant hydrogenase).